2018
DOI: 10.5334/irsp.118
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Dissonance: When Emotional Inconsistency Arouses Dissonance

Abstract: The aim of the two studies was to explore a new dissonance paradigm-expressive dissonance-based on the inconsistency between what people feel and what people express behaviorally. Expressive dissonance was aroused by asking participants to watch a film with a high emotional content, either positive (joy) or negative (sadness). In the no-dissonance condition, they received the instruction to naturally watch the film. In the expressive dissonance condition, they received the instruction to facially express emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…To our knowledge, only three studies have explored the intrapersonal impacts of expressive dissonance, specifically, smiling during a stressful task. Robinson and Demaree (2007) and Pelt et al (2018) found that relative to a control condition, participants who engaged in expressive dissonance (i.e. smiling) while watching negative film-clips displayed greater sympathetic nervous system arousal and performed poorly on a memory task assessing social and visual information presented in the film-clips.…”
mentioning
confidence: 99%
“…To our knowledge, only three studies have explored the intrapersonal impacts of expressive dissonance, specifically, smiling during a stressful task. Robinson and Demaree (2007) and Pelt et al (2018) found that relative to a control condition, participants who engaged in expressive dissonance (i.e. smiling) while watching negative film-clips displayed greater sympathetic nervous system arousal and performed poorly on a memory task assessing social and visual information presented in the film-clips.…”
mentioning
confidence: 99%